Tools for the USAID Global Food Security Strategy transition framework - CGIAR Research Program on Policies, Institutions, and Markets (2018)
The tool and corresponding instructions were provided to USAID in May 2018. The Global Food Security Strategy transition framework was approved by USAID Administrator Mark Green end 2018.